Digital technology and the metamorphosis in teacher education, 2020 - Esponda Versace , Laura (2024)
At a time of increasing demand for teachers with advanced digital skills, we took on the challenge of investigating the different parts of digital technology competencies. The objective of the study was to establish the level of relationship that exists between digital technology and the metamorphosis in teacher education. A study was carried out with a quantitative approach, hypothetical deductive method, cross-sectional and ordinal level. The impact, as a result of the Pandemic, has occurred in this educational context, transforming the teacher in their teaching strategies with effects in every corner of the world, not only from the technology itself but from pedagogy, communication, administration, in a framework of active participation of students, the promotion of an environment of respect as well as the evaluation of their learning. We worked on a sample of 60 teachers from different institutions at the basic education level, the method used was the analytical, the design used was the descriptive correlational, non-experimental design. We used the find for data collection and the questionnaire as an instrument. , validated by expert judgment. The results were obtained by descriptive statistics and for hypothesis testing, inferential statistics using Spearman's Rho statistician. A value of r= 0.73 was obtained according to the Spearman Correlation, and a sigma value of less than 0.05, thus rejecting the null hypothesis and accepting the hypothesis postulated in the study: digital technology has a highly significant relationship with the metamorphosis of the teacher teaching.